2020
DOI: 10.1123/jsr.2019-0206
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue-Related Changes in Running Gait Patterns Persist in the Days Following a Marathon Race

Abstract: Context: The risk of experiencing an overuse running-related injury can increase with atypical running biomechanics associated with neuromuscular fatigue and/or training errors. While it is important to understand the changes in running biomechanics within a fatigue-inducing run, it may be more clinically relevant to assess gait patterns in the days following a marathon to better evaluate the effects of inadequate recovery on injury. Objective: To use center of mass (CoM) acceleration patterns to investigate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Furthermore, some of these compensations were associated with the development of LLOIs. These findings build further on limited available literature that reported movement compensations and changes in movement dynamics after a fatiguing running [9][10][11][12]14] and prior LLOI occurrence [11,12]. In addition, in contrast to our previous study [10], we did find differences between the injured group and the uninjured group during steady state unfatigued running.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Furthermore, some of these compensations were associated with the development of LLOIs. These findings build further on limited available literature that reported movement compensations and changes in movement dynamics after a fatiguing running [9][10][11][12]14] and prior LLOI occurrence [11,12]. In addition, in contrast to our previous study [10], we did find differences between the injured group and the uninjured group during steady state unfatigued running.…”
Section: Discussionsupporting
confidence: 87%
“…Winter et al [11] did not find a decrease in step regularity, but did find a similar increase in RMS ratio in the ML direction in their male runners. In addition, Clermont et al [14] found that a marathon race induced a prolongated fatigue state 2 days following the race, characterized by an elevated peak ML acceleration and an increased RMS ratio ML in comparison to the day prior to the marathon race. Together with the results from this study, evidence is growing that running fatigue results in an increased variability in the ML direction already early in the run (from 30% onwards), and that these changes even persist days after the fatiguing run.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Correcting abnormal kinematics has been suggested to reduce the risk of injury [3,4]. Runners' gait parameters can also change during a prolonged run due to fatigue [5][6][7], which may increase injury risk as the runner deviates from their normal gait pattern [8,9]. Reducing injury risk factors via altering running biomechanics has been demonstrated to be feasible in a lab environment [4,10], but this requires sophisticated equipment and software.…”
Section: Introductionmentioning
confidence: 99%